2004
DOI: 10.21236/ada426059
|View full text |Cite
|
Sign up to set email alerts
|

Competency Based Future Leadership Requirements

Abstract: Public reporting burden for this collection of information is estimated to average lliour per response, Including the time for reviewing instaictlons, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regardng this burden estimate or any other aspect of this coUection of information, including suggestions for reducing this burden to Department of Defense, Washington HeaAguartens Services, Diractorata for Inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 42 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…In response to these efforts, the Center for Army Leadership (CAL) sponsored a leader competency study, which sought to produce a set of future leader requirements that would address changes in the Army's mission and force requirements in the future. This study was unique since it involved researchers with past experience in competency efforts with direct application to military and civilian organizations (Horey, Fallesen, Morath, Cronin, & Cassella, 2004). Researchers analyzed the future environment to examine how these changes might impact the Army's mission and force requirements and reviewed existing theories, research, and doctrine to derive a systems model of leaders and followers that identified the essential components and structures involved in the leadership process.…”
Section: Competency-based Researchmentioning
confidence: 99%
“…In response to these efforts, the Center for Army Leadership (CAL) sponsored a leader competency study, which sought to produce a set of future leader requirements that would address changes in the Army's mission and force requirements in the future. This study was unique since it involved researchers with past experience in competency efforts with direct application to military and civilian organizations (Horey, Fallesen, Morath, Cronin, & Cassella, 2004). Researchers analyzed the future environment to examine how these changes might impact the Army's mission and force requirements and reviewed existing theories, research, and doctrine to derive a systems model of leaders and followers that identified the essential components and structures involved in the leadership process.…”
Section: Competency-based Researchmentioning
confidence: 99%
“…Coordination is one of the roles of the CIMIC officer in PSO (Cockell 2002;De Coning 2005;JP 2003;Pugh 2001;Weinberger 2002). Social interaction is a primary function in the coordination of the military and humanitarian components (Horey et al 2004). The fundamental dimension of extrovert behaviour is more suited to enhance social interaction (Cloninger 1996;Crowne 2007;Ewen 1988).…”
Section: Sample Performance Ratingmentioning
confidence: 99%
“…According to Horey, Fallesen, Morath, Cronin, et al (2004), eight interpersonal competencies characterize the future Army leader. Three that have not already been addressed in previous sections are (1) vitalizing a positive climate; (2) arming self to lead; and (3) extending personal influence.…”
Section: Conceptual Competencementioning
confidence: 99%